The, of The Inhibitory Effect of Encapsulated Lemongrass Leaf Extract with Chitosan against Staphylococcus aureus and Streptococcus pyogenes : Daya Hambat Ekstrak Daun Serai Dapur yang Terenkapsulasi dengan Kitosan terhadap Staphylococcus aureus dan Streptococcus pyogenes - Komariah, Komariah; Rezky Anggraeni; Annisa, Fauziah Rahma; Febry, Febry (Universitas Airlangga, 2025)
The lemongrass plant (Cymbopogon citratus) was a potential medicinal plant due to the presence of secondary metabolites such as neral, citral, geranial acetate, flavonoids, and tannins, which possess pharmacological activities including antibacterial, antifungal, and antiinflammatory. However, the antibacterial secondary metabolites contained in lemongrass leaves were unstable, hence required a substance capable of encapsulating or entrapping them using other natural compounds such as chitosan and tripolyphosphate (TPP). The chitosan and TPP ratio significantly affects crosslinking during the encapsulation process. Staphylococcus aureus and Streptococcus pyogenes are among the bacteria potentially causing infections in the oral cavity. The aim of this research was to determine the inhibitory effect of encapsulated lemongrass leaf extract with chitosan and TPP ratios of 1:1, 1:0.9, 1:0.8, and 1:0.7 against S.aureus and S.pyogenes. The research results showed inhibition zones formed on S. aureus and S. pyogenes for each encapsulation ratio of 1:1, 1:0.9, 1:0.8, 1:0.7, were 25.09±0.62 mm, 21.01±0.13 mm, 22.78±0.39 mm, 23.96±0.14 mm, and 24.38±0.45 mm, 21.99±0.34 mm, 22.44±0.48 mm, and 20.49±0.24 mm, respectively. Encapsulation of lemongrass leaf extract using chitosan and TPP ratios was effective in inhibiting the growth of S. aureus and S. pyogenes, with the best ratio at 1:1. Keywords: Lemongrass leaves, encapsulation, chitosan, antibacterial, Staphylococcus aureus and Streptococcus pyogenes